Minimalisasi Konflik di Daerah: Mewujudkan Pemilu Secara Demokratis dengan Moral Agama - Rahman, Rini (Jurnal Demokrasi, 2008)
General election in Indonesia is a facility to emerge the power of Indonesian in order to result in Indonesian government that more democratic based on Pancasila and UUD 1945. Organizing a free, secret, honest, and fair direct general election can be implemented if all of the committees of general election have high integrity, professionalism, and accountability. However, some local conflicts affect on the democratic process getting worse. It is assumed that the conflict is caused by the lack of dependence of local KPUD (Committee for the Local Election). Thus, it needs a kind of action to minimize the local conflicts and to make the dependence of local KPUD as the main consideration to make the implementation of direct general election work well. It is also important to complete moral religious in practicing politics and direct general. Kata Kunci: Pemilu, Pilkada, Pemerintahan, Demokratis, Konflik, Komisi Pemilihan Umum (KPU)